2003
DOI: 10.1159/000074304
|View full text |Cite
|
Sign up to set email alerts
|

Azelastine Inhibits Secretion of IL-6, TNF-α and IL-8 as well as NF-κB Activation and Intracellular Calcium Ion Levels in Normal Human Mast Cells

Abstract: Background: Mast cells are involved in allergic inflammation by secreting histamine, proteases and several cytokines, including interleukin (IL)-6, tumor necrosis factor-α (TNF-α) and IL-8. Certain histamine-1 receptor antagonists, such as azelastine present in the ophthalmic solution Optivar®, have been reported to inhibit histamine and tryptase secretion, but its effect on inflammatory cytokine release from normal human umbilical cord blood-derived cultured mast cells (hCBMC) are not well known. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…Moreover, pretreatment of mast cells with diphenhydramine (50 µ M ), which totally blocks the H 1 receptor, could not prevent the ability of rupatadine to inhibit mast cells (results not shown). Rupatadine may inhibit intracellular calcium ion elevations and/or nuclear factor-ĸB activation, as previously shown for azelastine [29]. The ability of rupatadine to antagonize PAF may also somehow contribute to mast cell inhibition, especially if PAF is secreted from mast cells and has an autocrine stimulatory action.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, pretreatment of mast cells with diphenhydramine (50 µ M ), which totally blocks the H 1 receptor, could not prevent the ability of rupatadine to inhibit mast cells (results not shown). Rupatadine may inhibit intracellular calcium ion elevations and/or nuclear factor-ĸB activation, as previously shown for azelastine [29]. The ability of rupatadine to antagonize PAF may also somehow contribute to mast cell inhibition, especially if PAF is secreted from mast cells and has an autocrine stimulatory action.…”
Section: Discussionmentioning
confidence: 73%
“…For instance, azelastine resulted in a maximal inhibition of tryptase (55%) and histamine (41%) release [28], as well as of IL-6 (83%) release from hCBMCs at 24 µ M [25]. Azelastine also inhibited IL-6, IL-8 and TNF release from hCBMCs stimulated by IgE/anti-IgE [29]. More recently, the H 1 receptor antagonists [30] epinastine (40 µ M ) and azelastine (200 µ M ) reduced IL-8 release by almost 30%, epinastine and olopatadine reduced IL-10 release by 30–50%, while epinastine and olopatadine reduced TNF release by about 30% [30].…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that FEX is the most effective agent in terms of the suppression of TARC and MDC production from CD14+ cells after Cry j 1 stimulation. This conclusion may be supported by the observation that FEX exerted a significant suppressive effect at a concentration of 250 ng/ml, which is almost equal to therapeutic blood levels [18], but other agents, AZE, KET and OXA, required higher concentrations (approximately 1.5–2 times higher) than their therapeutic blood levels [19,20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…Many observations were reported upon evaluation of azelastine, including superior inhibition of IL6, tryptase and histamine secretion from mast cells over olopatadine (Kempuraj et al, 2002;Kempuraj et al, 2003). Azelastine is commonly formulated in combination with a corticosteroid; novel non aqueous formulations based on hydrofluoroalkane propellants offer promise in control of allergic rhinitis (Meltzer et al, 2014).…”
Section: Azelastinementioning
confidence: 99%